Variability of the f-cell ratio after treatment of traumatic hemorrhagic shock. (November 2018) - Khan, Faraz A.; Mullins, Richard; Ledgerwood, Anna M.; Lucas, Charles E.
Abstract: Purpose: Measuring total blood volume (TBV) in critically ill patients, using isotope techniques to determine red cell volume (RBCV) and plasma volume (PV) is laborious. Recently, PV measurement using a single bolus dose of tracers has been validated, thus, allowing TBV calculation using large venous hematocrit (LVHCT). However, this technique relies on using a correlation factor, the f-cell ratio, to adjust for differences in LVHCT and total body hematocrit (TBHCT). The normal f-cell ratio is 0.9 but has never been studied in patients recovering from hemorrhagic shock (HS). This study assesses the f-cell ratio at different phases after HS to determine accuracy in calculating TBV. Methods: 114 injured patients requiring immediate operation for HS were studied. All patients had measurements of PV and RBCV via isotope dilution enabling measurements of TBHCT. Correlation of LVHCT and TBHCT were used to calculate the f-cell ratio in the fluid sequestration (n = 81) and in the fluid mobilization period (n = 108). Results: The f-cell ratio (mean ± SD) averaged 0.89 ± 0.15 and 0.90 ± 0.01 in the first and second halves of the fluid sequestration period versus 0.90 ± 0.2 and 0.80 ± 0.07 in the first and second 48 h of the fluid mobilization period. The f-cell ratio was significantly lower (p=<0.001) in the mobilization period. Conclusions: These data show for the first time that using PV and LVHCT to calculate TBV after HS is unreliable. The mechanisms causing this variation in f-cell ratio is unknown but likely related to capillary/interstitial dynamics and needs further scientific study. Highlights: Accurate measurements of total blood volume in critically injured patients would be very helpful. Direct measurements of total blood volume blood components are very laborious. Total blood volume can be estimated using large venous hematocrit and a correction factor. The value of f cell ratio is not static during phases of recovery from hemorrhagic shock. Variability of f cell ration limits utilization in patients recovering from hemorrhagic shock.